Emergence of public sector performance auditing : a historical perspective / Nirmala Nath, Karen Van Peursem and Alan Lowe - Nath, Nirmala; Karen, Van Peursem; Alan, Lowe (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
The purpose of this paper is to evaluate the extant Anglo-American literature on 'performance auditing for the public sector', in order to identify the socioeconomic and political themes that influenced the emergence of public sector performance auditing. The paper also seeks to develop an understanding of the role and practice of performance auditing in the public sector. Common catalysts for change appear to rest in the influence of the local governmental senior auditor (e.g. Auditor General), the existence of public sector reform and changes in standardisation generally. The traditional role of the public sector auditor has undergone significant change over time. In particular, the scope of the public sector audit now exceeds the expectation that the auditor only check for regulatory and procedural compliance. It is now expected that the auditor enhance accountability in the management of public sector resources.